1987
DOI: 10.1073/pnas.84.14.5078
|View full text |Cite
|
Sign up to set email alerts
|

Depolarizing influences regulate preprotachykinin mRNA in sympathetic neurons.

Abstract: We have been studying mechanisms regulating neurotransmitter plasticity in sympathetic neurons. Neurons of the rat superior cervical ganglion (SCG) synthesize multiple putative transmitters, including the peptide substance P (SP). We have now examined steady-state levels of the mRNA encoding preprotachykinin (PPT), the SP precursor. A cloned cDNA probe was used to examine regulation mRNA levels in culture and in vivo. In RNA gel blot experiments, a single band (1.1 kilobases long) was observed in all cases in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…USA 89 (1992) neonatal ganglia, it appears to have some similarities with the increase in VIP-IR in adult ganglion. For example, in both cases there are increases in peptide content, in the number of immunostained neurons, and in the level ofthe corresponding mRNA (31). In addition, however, there are interesting differences between the two peptides.…”
Section: Discussionmentioning
confidence: 94%
“…USA 89 (1992) neonatal ganglia, it appears to have some similarities with the increase in VIP-IR in adult ganglion. For example, in both cases there are increases in peptide content, in the number of immunostained neurons, and in the level ofthe corresponding mRNA (31). In addition, however, there are interesting differences between the two peptides.…”
Section: Discussionmentioning
confidence: 94%
“…PPT mRNA was increased 25-fold in the explanted SCG. This effect could be inhibited by the depolarizing agent, veratridine, indicating a suppressive effect of physiological impulse activity on PPT synthesis (Roach et al, 1987). As with VIP, the elevation of SP immunoreactivity after axotomy is prevented by dexamethasone which also blocks SP expression induced by interleukin-lp (IL-1p; Hart et al, 1991;Kessler et al, 1993) or lipopolysaccharide (Shadiack et al, 1994).…”
Section: Substance P (Sp) Sp Was Originally Isolated Bymentioning
confidence: 97%
“…Multiple preprotachykinin (PPT) mRNAs arise from a single gene through alternate splicing of primary transcripts (Krause et al, 1987). Detection of low levels of PPT mRNA in the rat SCG (Roach et al, 1987) indicated that SP can be synthesized within sympathetic ganglia.…”
Section: Substance P (Sp) Sp Was Originally Isolated Bymentioning
confidence: 99%
“…Recent studies have shown that membrane depolarization causes not only rapid alterations in protein phosphorylation (Nairn et al, 1985), but also activation of new programs of gene expression in neuronal-type cells (Greenberg et al, 1985(Greenberg et al, , 1986Morgan and Curran, 1986;Black et al, 1987;Saffen et al, 1988;Bartel et al, 1989). Moreover, an increase in mRNA has been measured with stimuli causing the activation of Ca2+ and Na+ channels and membrane depolarization Morgan and Curran, 1986;Naranjo et al, 1986;Roach et al, 1987;Von Dreden et al, 1988). Genes regulated by depolarization include those that encode neuropeptides and neurotransmitter biosynthetic enzymes (Morris et al, 1988;Van Mguyen et al, 1990;Lu et al, 199 1).…”
mentioning
confidence: 99%